Analisis Hukum Terhadap Pemberian Transfusi Darah Di Rumah Sakit Berdasarkan Undang-Undang No. 44 Tahun 2009 Tentang Rumah Sakit - Ratna Suminar, Sri (LPPM Unisba, 2011)
Blood transfusion has played a very important role for cure and recovery of patient health. However, blood transfusion treatment in hospital is generally unsafe, and even it also threatens the life of patient caused by several factors. The first factor is due to negligence on the part of the medical personnel either prior to or during the blood transfusion. The second one is lack of both medical and non-medical equipement toÂ Â keep andÂ distribute blood, so that blood is unsafe to be transfused. Actually, under Law No.14 of 2009 Concering Hospital, hospital is obliged to provide the blood transfusion.